Law, sex, and Christian society in medieval Europe - Brundage, James A. (University of Chicago Press, 1987)
"Brundage's book is consistently learned, enormously useful, and frequently entertaining. It is the best we have on the relationships between theological norms, legal principles, and sexual practice."--Peter Iver Kaufman, Church History